2015
DOI: 10.1111/bph.13380
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin‐1 contributes to the progression of renal injury in sickle cell disease via reactive oxygen species

Abstract: BACKGROUND AND PURPOSEEndothelin-1 (ET-1) is increased in patients with sickle cell disease and may contribute to the development of sickle cell nephropathy. The current study was designed to determine whether ET-1 acting via the ET A receptor contributes to renal injury in a mouse model of sickle cell disease. EXPERIMENTAL APPROACHAdult, humanized HbSS (homozygous for sickle Hb) mice had increased ET-1 mRNA expression in both the cortex and the glomeruli compared with mice heterozygous for sickle and Hb A (Hb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 68 publications
1
40
0
Order By: Relevance
“…This is also correct. Published data evidence the involvement of oxidative stress (79,100,105,108,113,115,116,121,123,132,134,135), inflammation (9, 22, 27, 32, 101, 105-108, 115, 124-127, 134), dyslipidemia (135)(136)(137)(138), microparticles (89,122,123,139), and vasoactive peptides (110,111,(140)(141)(142)(143). These additional pathways (depicted in Figure 2) are potentially additive or synergistic to intravascular hemolysis-like mechanisms.…”
Section: Controversies Regarding the Hyperhemolysis Modelmentioning
confidence: 99%
“…This is also correct. Published data evidence the involvement of oxidative stress (79,100,105,108,113,115,116,121,123,132,134,135), inflammation (9, 22, 27, 32, 101, 105-108, 115, 124-127, 134), dyslipidemia (135)(136)(137)(138), microparticles (89,122,123,139), and vasoactive peptides (110,111,(140)(141)(142)(143). These additional pathways (depicted in Figure 2) are potentially additive or synergistic to intravascular hemolysis-like mechanisms.…”
Section: Controversies Regarding the Hyperhemolysis Modelmentioning
confidence: 99%
“…These results suggest that ET A activation contributes to the maintenance of dysfunction of the glomerular filtration barrier in established sickle nephropathy, a finding that is consistent with previous results from our laboratory. 22 We also determined if ETsignaling contributes to the maintenance of tubular injury in SCD, because final urinary albumin excretion is the result of both glomerular filtration and proximal tubular uptake. Thus, we measured urinary excretion of kidney injury marker 1 (KIM-1) and N-acetyl-b-Dglucosaminidase (NAG), markers of proximal tubule injury.…”
Section: Short-term Et Receptor Antagonism Attenuates Glomerular and mentioning
confidence: 99%
“…17 In the kidney, ET-1 has been implicated as a mechanistic contributor to development of proteinuria in various forms of CKD. [18][19][20][21][22] Moreover, the elevated urinary ET-1 excretion reported in patients with SCD correlates with microalbuminuria, 23 suggesting a pathophysiologic link between ET-1 induction and renal injury in SCD. Direct evidence to demonstrate that ET-1 contributes to renal dysfunction in SCD comes from a study by Sabaa and colleagues who reported that SCD mice treated with the dual ET receptor antagonist, bosentan, were protected from hypoxiainduced decreases in renal blood flow and renal inflammation.…”
mentioning
confidence: 99%
“…ET-1 mediates endothelial dysfunction by reducing NO bioavailability and induces direct injury to podocytes via the ETA receptor [9,10]. In sickle cell mouse models, ET-1 has been demonstrated to mediate glomerular injury via reactive oxygen species, and ETA receptor antagonism appears to afford renal protection [11,12]. In patients with SCD, ET-1 has also been demonstrated to be associated with albuminuria and measures of vascular dysfunction [13].…”
Section: Pathophysiology Of Sickle Cell Nephropathymentioning
confidence: 99%